Spontaneous resolution of colloid cyst of the third ventricle: Implications for management - Turel, Mazda; Kucharczyk, Walter; Gentili, Fred (Asian Journal of Neurosurgery, 2017)
While there is little controversy regarding the treatment of symptomatic colloid cysts, the optimal management of “incidentally” detected and asymptomatic colloid cyst remains unclear. The age of the patient, duration and significance of symptoms related to the cyst, size and radiological characteristics of the cyst and the presence of hydrocephalus are all factors to be considered before considering surgery. While surgery most often provides good results in the majority of patients, complications do occur. Despite growing literature about the natural history of this condition, to date, only three cases of spontaneous resolution of colloid cyst <10 mm have been reported. We report the case of spontaneous resolution of a colloid cyst larger than 10 mm, initially managed with close observation and serial neuroimaging. This case highlights the possible role for a conservative approach even in larger-sized cysts.
Keywords: Colloid cyst; natural history; radiology; spontaneous resolution